Changes in the Intermediate Water Masses of the Mediterranean Sea During the Last Climatic Cycle—New Constraints From Neodymium Isotopes in Foraminifera. Issue 4 (20th April 2021) - Colin, Christophe; Duhamel, Maxence; Siani, Giuseppe; Dubois‐Dauphin, Quentin; Ducassou, Emmanuelle; Liu, Zhifei; Wu, Jiawang; Revel, Marie; Dapoigny, Arnaud; Douville, Eric; Taviani, Marco; Montagna, Paolo
Abstract: Variations in Mediterranean thermohaline circulation of the Quaternary are still not well constrained whereas they have been considered to have an influence on the Atlantic Meridional Overturning Circulation and on the oxygenation of waters in the deep basins of the Mediterranean Sea. εNd analyses have been carried out on planktonic foraminifera of cores collected in the central Mediterranean Sea to constrain water mass exchange between the Eastern and Western Mediterranean Sea (EMS and WMS) during the last climatic cycle. εNd records from the WMS and EMS display similar higher values during warm substages of interglacial Marine Isotopic Stage (MIS) 1 and 5. This suggests an efficient connection between the two Mediterranean sub‐basins and the transfer of radiogenic waters to the Tyrrhenian Sea via the Levantine Intermediate Water (LIW). Conversely, during glacial MIS, εNd of the intermediate depth of the Tyrrhenian Sea are less radiogenic than the EMS, implying limited hydrological connection between sub‐basins during low sea‐level stands. Superimposed on these glacial‐interglacial variations, increased εNd occurred during Heinrich Stadial events. This suggests a reduction in the formation of unradiogenic WIW in the Gulf of Lions due to the input of relatively fresh surface Atlantic water to the WMS and/or the inflow of radiogenic glacial LIW and upper EMDW to the Tyrrhenian Sea as a result of an active EMS convection related to saltier and colder conditions. Such potential millennial‐scale pulses of LIW intrusion into the Tyrrhenian Sea may have led to an enhanced Mediterranean Outflow Water intensity in the Gibraltar Strait. Key Points: First εNd record of the central Mediterranean Sea during the last climatic cycle Reconstruction of water exchanges variations between the eastern and western Mediterranean basins during the last climatic cycle Evidence of millennial‐scale variations of εNd during the last glacial time indicating pulses of LIW intrusion into the Tyrrhenian Sea